Makna Keindahan dalam Iklan Digital Pariwisata Bahari Pantai Sawarna Banten di Youtube (Analisis Semiotika Charles S. Prierce) - Dudi Hartono (Universitas Majalengka, 2021)
Tourism is a potential regional income, so that various regions are competing to market the tourism potential in their respective countries. Tourism promotion using video has become a popular choice because it is easy to place it on the youtube channel. The problem that arises is how then the video reaches the expected target audience. Seeing these data, it is important how to use digital advertising on the YouTube channel as a promotional and marine media, in this case Sawarna beach. Digital advertising, audio-visual, has advantages on the visual side because the audience can see firsthand the beauty of the beach. In addition, the YouTube channel supports its worldwide reach. YouTube audio-visual ads have elements such as shots, colors, backsound and graphics, as semiotic signs, all of which work to form a unified meaning. Through semiotic analysis the author wants to see how the signs used by advertising producers in forming the expected meaning? And how do the producers of these advertisements use certain signs to form the desired meaning?